To Study the Development of the Leading Tech Stocks Performance Growth in Comparison Against the Market Index of NYSE - Dr Yeoh Wee Win (European Science Publishing, 2023)
The research had been initiated to study the development of the leading tech stocks performance growth in comparison against the market index of New York Stock Exchange (NYSE). The research outlook had been highlighted from the problem statement arises emphasizing on the research questions addressing the gap in the understanding on the relationship between the tech stocks performance and market index performance as well as testing for the presence in the higher performance in the tech stocks industry towards the market benchmark. With the research objective being designed, the methodology of the research had proposed on the application of the quantitative study including the reliability test, correlation analysis and regression analysis. The study will include the sample of 15 stocks from the tech industry using selective sampling to identify the leading tech companies where the data collection will include the timeline of ten years from 2011 to 2020. In addition, the comparative analysis had been introduced to extend the study to create the clear comparison between the performance growth between the tech stocks and the market index of NYSE. The findings and results for the study had been contributing to the understanding on the presence of the significant positive relationship between the major tech stocks and the NYSE market index. In addition, the comparative analysis had shown sufficient evidence toc conclude that the tech stock growth is consistently achieving higher growth and return over the market index growth over the past ten years. The outcome of study had concluded that the higher potential growth over other industries which could signal the future trend of tech industry growth moving forward into the future.
Keywords: New York Stock Exchange, tech industry, stocks, technology, leading tech companies.